The Identification of Hysterothlacium on Sixbar Groupers (Epinephelus sexfasciatus) in The Territorial Waters of East Java Using Sequencing Method: Identifikasi Hysterothylacium sp. pada Ikan Kerapu Belang (Epinephelus sexfasciatus) di Perairan Jawa Timur Menggunakan Metode Sekuensing - Kismawardani, Putri; Koesdarto , Setiawan; Santoso , Kuncoro Puguh; Lastuti , Nunuk Dyah Retno; Sabdoningrum , Emy Koestanti; Kusnoto (Faculty of Veterinary Medicine Universitas Brawijaya, 2023)
This study aimed to identify the parasitic nematode Hysterothylacium sp. using the sequencing method. A sampling of Hysterothylacium sp. was taken from 60 striped grouper fish (Ephinephelus sexfasciatus) and has characteristics such as brown color, booring teeth on the anterior, a simple digestive system including the esophagus, stomach (ventriculus), small intestine and does not have mucron on the posterior. Specific primers for the COX-2 mtDNA gene (210F and 211R) were used for DNA amplification (Polymerase Chain Reaction) and DNA sequencing with a length of 629bp. The positive result of the PCR method (sample S) was sequenced. Then, the results of the sequencing method were compared with the reference DNA sequences KY065298.1, MF120253.1, MF120248.1, and KU886687.1. Furthermore, Homology and kinship tests were carried out using GenBank (NCBI). Results showed a 97% similarity of the sample with Hysterothylacium amoyense cytochrome oxidase subunit II (COX-2) gene MF120253.1.